2022
DOI: 10.1037/ccp0000714
|View full text |Cite
|
Sign up to set email alerts
|

The temporal relationships between therapist adherence and patient outcomes in dialectical behavior therapy.

Abstract: Objective: Although Dialectical Behavior Therapy (DBT) is a well-established evidence-based psychotherapy, little is known about the role of therapist adherence in promoting positive outcomes. This study evaluated the temporal relationships between therapist adherence to DBT and patient outcomes, as well as potential moderators of these relationships. Method: Data were from six clinical trials conducted in research and community settings with a variety of patient populations. In these trials, trained observers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…expert therapist videos explaining key therapeutic concepts and skills, digital apps), with measurement‐based care involving real‐time monitoring of patient outcomes used to inform and adjust treatment strategies to optimize treatment benefits (e.g. clinical dashboards illustrating self‐harm outcomes; Asarnow et al., 2020; Craske et al., 2009; Harned, Gallop, Schmidt, & Korslund, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…expert therapist videos explaining key therapeutic concepts and skills, digital apps), with measurement‐based care involving real‐time monitoring of patient outcomes used to inform and adjust treatment strategies to optimize treatment benefits (e.g. clinical dashboards illustrating self‐harm outcomes; Asarnow et al., 2020; Craske et al., 2009; Harned, Gallop, Schmidt, & Korslund, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…sleep deprivation, assumption of parental roles, negotiating partner needs and feeding challenges) corroborate a need for inclusion of coaching services to support skills use. Finally, although none of the reviewed studies assessed treatment fidelity, findings from Harned et al (2022) indicated that therapist adherence to DBT predicts therapeutic outcomes, particularly for high‐risk concerns such as hospitalisation, suicide attempts and early dropout. As such, outcomes for high‐risk perinatal individuals, including caregivers with elevated risks of suicide, self‐harm or serious mental illness, are likely to be optimised through the provision of comprehensive and adherent DBT.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly concerning given that therapists in routine practice often deliver DBT non-adherently according to this study (44% of sessions) and prior research (48% of sessions; Harned et al, 2021a , b ). Moreover, many clients who receive DBT are at high risk for suicide and therapist adherence is an important mechanism by which suicidal behavior is reduced (Harned et al, 2022 ). The DBT AC-I represents a significant advance towards enabling stakeholders to evaluate if the treatment being provided is consistent with DBT as it is defined in the treatment manual.…”
Section: Implications and Next Stepsmentioning
confidence: 99%
“…Therapist adherence is a core component of fidelity and refers to the degree to which therapists deliver the treatment procedures as intended (Perepletchikova et al, 2007 ). In DBT, higher therapist adherence leads to better outcomes for clients (Harned et al, 2022 ), making it a particularly important target for implementation and quality assurance efforts.…”
mentioning
confidence: 99%
See 1 more Smart Citation